Biotechnology and Biopharmaceuticals Transforming proteins and genes into drugs - Ho, Rodney J Y (Wiley-Liss, 2003)
The first of this book's three sections focuses on the process of transforming a macromolecule into a therapeutic agent; the second provides a brief overview of each class of macromolecule with respect to physiological role and clinical application. The second section also provides additional detail for each FDA approved biopharmaceutical. The final section looks to new advances that will enhance our ability to develop new macromolecules into effective biopharmaceuticals.